GERAKAN SOSIAL TERHADAP MASALAH PEMBANGUNAN BENDUNGAN KRUENG PASEE KABUPATEN ACEH UTARA - Humaira, Suci; Nazaruddin, M.; Fakhrurrazi, Fakhrurrazi; Maliati, Nulwita; Ketaren, Amiruddin (FISIP Universitas Malikussaleh, 2025)
This research examines social movements on the issue of Krueng Pasee dam construction (Case Study in Nibong Subdistrict, North Aceh District). The main focus of this study is social movement activities related to the Krueng Pasee dam construction issue and the forms of social movements. This research uses Anthony Giddens' social movement theory. The research method used in this study is a qualitative method with a descriptive approach. The data in this research comes from primary data, namely from the results of observations, and interviews while the secondary data in this research is documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the activities carried out by the Samudera Youth Forum (FPS), community leaders, and the community in the social movement related to the construction of the Krueng Pasee Dam in North Aceh consisted of three stages, namely before the movement occurred, when the movement occurred, and after the movement occurred with the form of movement action being demonstrations, raising community support and social media. Each stage includes activities that aim to achieve the success of the movement. This social movement succeeded in achieving its goal by influencing the local government's decision to immediately start the construction of the Krueng Pasee dam. This success shows the effectiveness of social movements in voicing community unrest and encouraging the local government to take action.